(untitled) (Physical Education, Health and Social Sciences, 2025)
The concept of cognitive reserve was developed to elucidate the distinction between the clinical and intellectual consequences of brain injury and the objective level of pathology. The structural (brain reserve) and functional (brain maintenance, resilience, and compensation) components of neural tissue constitute the cognitive reserve. These components reflect exposome-driven lifelong plasticity, which determines the brain’s resilience to aging and disease. Adaptive alterations in neurons and brain networks constituted the primary focus of this concept’s molecular foundation. We advocate for a more comprehensive perspective by presenting evidence that neuroglia play a significant role in defining the cognitive reserve through homeostatic, neuroprotective, and neurodegenerative processes. The development of the brain connectome and synaptically connected neuronal circuits, which determine cognitive reserve, depends on neuroglia throughout life. While neuroglia’s regenerative capacities are essential for brain compensation in disease, neuroglial homeostatic and protective physiological responses characterize brain maintenance and resilience. An innovative strategy to extend cognitive lifespan may be to target neuroglia.